Oxygen at Nanomolar Levels Reversibly Suppresses Process Rates and Gene Expression in Anammox and Denitrification in the Oxygen Minimum Zone off Northern Chile - Tage Dalsgaard; Frank J. Stewart; Bo Thamdrup; Loreto De Brabandere; Niels Peter Revsbech; Osvaldo Ulloa; Don E. Canfield; Edward F. DeLong (mBio, 2014)
ABSTRACT A major percentage (20 to 40%) of global marine fixed-nitrogen loss occurs in oxygen minimum zones (OMZs). Concentrations of O2 and the sensitivity of the anaerobic N2-producing processes of anammox and denitrification determine where this loss occurs. We studied experimentally how O2 at nanomolar levels affects anammox and denitrification rates and the transcription of nitrogen cycle genes in the anoxic OMZ off Chile. Rates of anammox and denitrification were reversibly suppressed, most likely at the enzyme level. Fifty percent inhibition of N2 and N2O production by denitrification was achieved at 205 and 297 nM O2, respectively, whereas anammox was 50% inhibited at 886 nM O2. Coupled metatranscriptomic analysis revealed that transcripts encoding nitrous oxide reductase (nosZ), nitrite reductase (nirS), and nitric oxide reductase (norB) decreased in relative abundance above 200 nM O2. This O2 concentration did not suppress the transcription of other dissimilatory nitrogen cycle genes, including nitrate reductase (narG), hydrazine oxidoreductase (hzo), and nitrite reductase (nirK). However, taxonomic characterization of transcripts suggested inhibition of narG transcription in gammaproteobacteria, whereas the transcription of anammox narG, whose gene product is likely used to oxidatively replenish electrons for carbon fixation, was not inhibited. The taxonomic composition of transcripts differed among denitrification enzymes, suggesting that distinct groups of microorganisms mediate different steps of denitrification. Sulfide addition (1 µM) did not affect anammox or O2 inhibition kinetics but strongly stimulated N2O production by denitrification. These results identify new O2 thresholds for delimiting marine nitrogen loss and highlight the utility of integrating biogeochemical and metatranscriptomic analyses. IMPORTANCE The removal of fixed nitrogen via anammox and denitrification associated with low O2 concentrations in oceanic oxygen minimum zones (OMZ) is a major sink in oceanic N budgets, yet the sensitivity and dynamics of these processes with respect to O2 are poorly known. The present study elucidated how nanomolar O2 concentrations affected nitrogen removal rates and expression of key nitrogen cycle genes in water from the eastern South Pacific OMZ, applying state-of-the-art 15N techniques and metatranscriptomics. Rates of both denitrification and anammox responded rapidly and reversibly to changes in O2, but denitrification was more O2 sensitive than anammox. The transcription of key nitrogen cycle genes did not respond as clearly to O2, although expression of some of these genes decreased. Quantifying O2 sensitivity of these processes is essential for predicting through which pathways and in which environments, from wastewater treatment to the open oceans, nitrogen removal may occur.